Loss Reduction Method for the Isolated qZS-based DC/DC Converter - Zakis, Janis; Rankis, Ivars; Liivik, Liisa (Electrical, Control and Communication Engineering, 2013)
This paper presents an isolated quasi-Z-source inverter-based (qZSI) resonant DC/DC converter. The explanation of selection of the proposed topology is justified. Both the normal and the boost modes are discussed. Theoretical operation waveforms as well as basic expressions for the calculation of currents and voltages are proposed. A 1500 W laboratory prototype was built and experimentally verified at two operation points: that of light-load (300 W) and full-load (1500 W). All the experiments were also carried with resonant circuit and without it. The experimental results as well as performance of proposed qZSI based resonant DC/DC converter laboratory setup are presented and analyzed. Experimental and calculated characteristics showing the dependence of the load voltage and supply current on the load resistance in both modes were presented. The dynamic losses in the transistors were evaluated for the cases with the resonant circuit and without it. The main conclusions based on this study are summarized and the future tasks for development of proposed converter were defined.